Protect or plunder? : understanding intellectual property rights - Shiva, Vandana (London : Zed Books, 2001)
Social Science
Keywords: Intellectual property - Patents; Intellectual prperty - Rights; Global economy; Biodiversity; Democracy; Dictatorship